2023
DOI: 10.1002/bdr2.2180
|View full text |Cite
|
Sign up to set email alerts
|

Areca nut and smokeless tobacco exposure induces micronucleus, other nuclear abnormalities and cytotoxicity in early chick embryo

Abstract: Areca nut (AN) and smokeless tobacco (SLT) are indiscriminately consumed among the populations of Southeast and South Asian countries, even by women during the gestational period. This study aimed to investigate the genotoxic and cytotoxic potentials of AN and Sadagura (SG), a unique homemade SLT preparation, alone and in combination in early chick embryos. Fertile white leghorn chicken eggs were randomly divided into five treatment groups: vehicle control, positive control (Mitomycin C, 20 μg/egg), AN, SG, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Nicotine exposure at early developmental stages affects the embryonic survival rate and is accountable for over five million premature deaths across the world annually [23]. The genotoxic and cytotoxic potential of Areca nut and smokeless tobacco were described [24]. In the study conducted by Shan et al [19,25] to observe the survival of nicotine-administered chick embryos observed a 90% survival rate in the control group and in that exposed to green tea extract, a 20% survival rate in the group administered nicotine, and a survival rate of 50% in the chicks exposed to both nicotine and green tea extract.…”
Section: Lower Survival Ratementioning
confidence: 99%
“…Nicotine exposure at early developmental stages affects the embryonic survival rate and is accountable for over five million premature deaths across the world annually [23]. The genotoxic and cytotoxic potential of Areca nut and smokeless tobacco were described [24]. In the study conducted by Shan et al [19,25] to observe the survival of nicotine-administered chick embryos observed a 90% survival rate in the control group and in that exposed to green tea extract, a 20% survival rate in the group administered nicotine, and a survival rate of 50% in the chicks exposed to both nicotine and green tea extract.…”
Section: Lower Survival Ratementioning
confidence: 99%